Cognitive-Behavioral Therapy and Neuroscience: Towards Closer Integration - Jokić-Begić, Nataša (2010)
The aim of this review article is to provide an integrative perspective by combining basic assumptions of cognitive behavioral therapy (CBT) with neuroscience research results. In recent years, interdisciplinary research in the field of neuroscience has expanded our knowledge about neurobiological correlates of mental processes and changes occurring in the brain due to therapeutic interventions. The studies are largely based on non-invasive brain imaging techniques, such as functional neuroimaging technologies of positron emission tomography (PET) and functional magnetic resonance imaging (fMRI). The neuroscientific investigations of basic CBT hypotheses have shown that (i) functional and non-functional behavior and experiences may be learned through lifelong learning, due to brain neuroplasticity that continues across the entire lifespan ; (ii) cognitive activity contributes to dysfunctional behavior and emotional experience through focusing, selective perception, memory and recall, and characteristic cognitive distortion ; on a neurobiological level, there is a relationship between top-down and bottom-up regulation of unpleasant emotional states ; and (iii) cognitive activity may be changed, as shown by therapeutic success achieved by metacognitive and mindfulness techniques, which also have their neurobiological correlates in the changes occurring in the cortical and subcortical structures and endocrine and immune systems. The empirical research also shows that neurobiological changes occur after CBT in patients with arachnophobia, obsessive- compulsive disorder, panic disorder, social phobia, major depressive disorder and chronic fatigue syndrome.disorder and chronic fatigue syndrome.
Projekt MZOS
ENG